2014
DOI: 10.1007/s10396-014-0548-6
|View full text |Cite
|
Sign up to set email alerts
|

HDlive imaging of fetal enteric duplication cyst

Abstract: Enteric duplication cysts are rare congenital anomalies, but their antenatal diagnosis is becoming more common because of advances in ultrasonography. With the latest state-of-the-art technology, HDlive facilitates a more realistic anatomical visualization of different fetal organ structures, making diagnosis more precise. We present a case of antenatal HDlive imaging of an enteric duplication cyst. A 26-year-old pregnant Japanese woman was referred to our ultrasound clinic because of a fetal intra-abdominal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…It is a rare cystic lesion usually located in the small intestine, particularly in the ileus. 21 2D sonography shows a thick-walled cyst with heterogeneous internal echoes (Fig. 22A).…”
Section: Enteric Duplication Cystmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a rare cystic lesion usually located in the small intestine, particularly in the ileus. 21 2D sonography shows a thick-walled cyst with heterogeneous internal echoes (Fig. 22A).…”
Section: Enteric Duplication Cystmentioning
confidence: 99%
“…22A). 21 HDlive provides a more discernible image of a rounded structure with a thick wall, no communication with other intra-abdominal structures, and presence of large amounts of thick debris inside which can be visualized with conventional 2D sonography (Fig. 22B).…”
Section: Enteric Duplication Cystmentioning
confidence: 99%
See 1 more Smart Citation
“…Several Authors have focused on 3D US as a complementary tool in the evaluation of the secondary palate (25)(26)(27)(28)(29)(30)(31)(32) or the fetal mandible (24,33), and recent reports have suggested that the subjective (34)(35)(36)(37)(38)(39)(40) or semiautomated (41) detection of facial dysmorphisms using 3D US can contribute in the identification of highly suggestive features of genetic syndromes. Also skeletal (42)(43)(44), cardiac (45)(46)(47)(48)(49)(50)(51)(52)(53) and thoracoabdominal (54,55) imaging may benefit from 3D US assessment, while more recent advances in 3D imaging have focused on the implementation of intelligent software for the automated data extraction from 3D volume datasets for clinical purposes. Within this scenario, fetal intelligent navigation (56)(57)(58)(59) and the 5D CNS+ (60) software have been designed with the aim to provide the clinicians valuable and reliable tools capable to simplify the ultrasound assessment of the fetal heart and brain, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…HDlive uses an adjustable light source, creating lighting and shadowing effects, thereby increasing depth perception, to generate realistic images of the normal fetus and fetal anomalies. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Using the HDlive silhouette mode, we can obtain novel information on normal fetal structures, congenital deformities, and placental abnormalities. [18][19][20][21] It can visualize outlines of structures of interest at the same time as visualizing the inner core, meaning that it is more effective for identifying normal anatomy and congenital deformities.…”
Section: Introductionmentioning
confidence: 99%